ChemInform Abstract: Water‐Based Conditions for the Microscale Parallel Synthesis of Bicyclic Lactams. Issue 22 (13th May 2013) - Malaquin, Sandra; Jida, Mouhamad; Courtin, Justin; Laconde, Guillaume; Willand, Nicolas; Deprez, Benoit; Deprez‐Poulain, Rebecca
Abstract Simple conditions are developed for the reaction of keto acids with dinucleophiles.